2009
DOI: 10.1038/cdd.2009.120
|View full text |Cite
|
Sign up to set email alerts
|

Features of programmed cell death in intact Xenopus oocytes and early embryos revealed by near-infrared fluorescence and real-time monitoring

Abstract: Factors influencing apoptosis of vertebrate eggs and early embryos have been studied in cell-free systems and in intact embryos by analyzing individual apoptotic regulators or caspase activation in static samples. Described here is a novel method for monitoring caspase activity in living Xenopus oocytes and early embryos. The approach, utilizing microinjection of a near-infrared caspase substrate that emits fluorescence only after its proteolytic cleavage by active effector caspases, has enabled the elucidatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…ns, not significant; *P<0.05; **P<0.005 (Student's t-test). Garrod et al, 2012;Hawkins et al, 1999;Johnson et al, 2009;Khanna et al, 2010;Yamaguchi et al, 2011;Zhang et al, 2009). Most of these reporters make use of the fluorescence resonance energy transfer (FRET) technology or a surface plasmon resonance imaging system, in which the fluorescent signal is lost after caspase cleavage (Park et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…ns, not significant; *P<0.05; **P<0.005 (Student's t-test). Garrod et al, 2012;Hawkins et al, 1999;Johnson et al, 2009;Khanna et al, 2010;Yamaguchi et al, 2011;Zhang et al, 2009). Most of these reporters make use of the fluorescence resonance energy transfer (FRET) technology or a surface plasmon resonance imaging system, in which the fluorescent signal is lost after caspase cleavage (Park et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The size also allows injections to alter ionic composition or regulate the activity of different proteins (Dascal, 1987). Previous studies have shown that the X. laevis oocyte displays a normal apoptotic process, which includes activation of caspases, cytochrome c release from the mitochondria, nuclear condensation and ATP depletion (Braun et al, 2003;Johnson et al, 2010;Nutt et al, 2005;Tokmakov et al, 2011). The expression level of endogenous channels is low (Dascal, 1987) and this makes them suitable to explore the importance of ion channels and intracellular ion concentrations in the apoptotic process.…”
Section: 3mentioning
confidence: 99%
“…laevis oocytes display a normal apoptotic process compared to other cells including cytochrome c release and activation of caspase-3 (Braun et al, 2003;Johnson et al, 2010;Nutt et al, 2005;Tokmakov et al, 2011). In papers I-III, caspase-3 activity was measured by the fluorescence of 7-amino-4-methylcoumarin (AMC) resulting from the cleavage of acetyl Asp-Glu-Val-Asp 7-amido-4-methylcoumarin (Ac-DEVD-AMC) by activated caspase-3.…”
Section: Induction and Detection Of Apoptosismentioning
confidence: 99%
“…Proteins-Five members of the Xenopus Bcl-2 family of proteins (xBcl-w/xR1, xBcl-x L /xR11, xBax, xBid, and xBok) were functionally characterized in the previous studies (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). In addition, partial or complete nucleotide sequences of 10 Bcl-2 family proteins (xBcl-2, xBcl-B, xBcl-G, xBcl2L12, xBcl2L13, xMcl-1, xBak, xBim, xBmf, and xNoxa) were deposited in the Xenopus nucleotide database, but the functions of their protein products remained uncharacterized (42)(43)(44).…”
Section: Identification and Rt-pcr Analysis Of Xenopus Bcl-2 Familymentioning
confidence: 99%
“…They are classified as either anti-apoptotic or pro-apoptotic, and the functional balance between these two groups controls the mitochondria-mediated intrinsic pathway of apoptosis. Although more than 10 members of the Bcl-2 family of proteins have been identified in Xenopus laevis (simply referred to as Xenopus hereafter), their functional characterizations are not yet complete (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19).…”
mentioning
confidence: 99%